Nutritional genomics : (Wiley-Interscience, 2006)
Nutrigenomics provides an integrated and up-to-date overview of the fundamental principles and scientific methodologies that serve as the foundation for nutrigenomics. World-renowned experts in the field of nutrigenomics have contributed their latest breakthroughs and insights in their particular areas of expertise. While each chapter can be used as a complete, stand-alone unit, they are all organized so that the chapters build on each other, leading the reader smoothly from basic principles to more complex scientific findings and experimental designs. Moreover, scientifically focused chapters are carefully balanced with those addressing the social, ethical, regulatory, and commercial implications of nutrigenomics